Analisa Sentimen Review Hotel Menggunakan Algoritma Support Vector Machine Berbasis Particle Swarm Optimization - Elly Indrayuni (Evolusi : Jurnal Sains dan Manajemen, 2016)
Abstract - Hotel is one of the most important tourism product to be considered both in terms of facilities, services or mileage and travel. We have had many travel websites that provide the facility for internet users write opinions and personal experiences online. Sentiment analysis or opinion mining is one solution to overcome the problem of classifying opinions or reviews into positive or negative opinion automatically. The technique used in this study is Support Vector Machines (SVM). SVM is able to identify the separate hyperplane that maximizes the margin between two different classes. The accuracy of the resulting value will be the benchmark to find the best test model for sentiment classification case. The evaluation was done using 10 fold cross validation. The results showed an increase in accuracy of 5.61% for Support Vector Machine algorithm from 91.33% to 96.94% after the application of selection features Particle Swarm Optimization. Keywords: Sentiment Analysis, Review, Support Vector Machines, Particle Swarm Optimization Abstrak - Hotel merupakan salah satu produk pariwisata yang sangat penting untuk dipertimbangkan baik dari segi fasilitas, pelayanan ataupun jarak tempuh perjalanan wisata. Saat ini sudah banyak website wisata yang menyediakan fasilitas untuk pengguna internet menuliskan opini dan pengalaman pribadinya secara online. Analisa sentimen atau opinion mining merupakan salah satu solusi mengatasi masalah untuk mengelompokan opini atau review menjadi opini positif atau negatif secara otomatis. Metode yang digunakan pada penelitian ini adalah Support Vector Machine. SVM mampu mengidentifikasi hyperplane terpisah yang memaksimalkan margin antara dua kelas yang berbeda. Nilai akurasi yang dihasilkan akan menjadi tolak ukur untuk mencari model pengujian terbaik untuk kasus klasifikasi sentimen. Evaluasi dilakukan menggunakan 10 fold cross validation. Hasil penelitian menunjukkan peningkatan nilai akurasi sebesar 5.61% untuk algoritma Support Vector Machine dari 91.33% menjadi 96.94% setelah penerapan seleksi fitur Particle Swarm Optimization. Kata Kunci: Analisa sentimen, Review, Support Vector Machines, Particle Swarm Optimization